Influence of Iron Oxide Powders on Braking Performance of Brake Friction Materials / R.J. Talib...[et al.] - Talib, R.J.; Basri, M. Hisyam; Ismail, N.I.; Rabilah, R. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Friction material is used to slow down the moving vehicle and finally stopped at the required position by the pressing it against the rotating brake disc. Four friction material formulations marked as T, T1, T2 and T3 have been prepared through powder metallurgy process. The effect of different volume percentage (vol. %) iron oxide on the braking performance will be the main focus of this study. Each sample was subjected to porosity, hardness, friction and wear in accordance with international standard test procedures. The three samples T1, T2 and T3 which were utilising of activated carbon from kernel shell (PKS carbon) as their carbon content had higher coefficient of friction (COF) than sample which was using commercial carbon, sample T. Thus, PKS carbon produced locally could be used to replace the imported commercial carbon. Sample T2 which was composed of 15% voulme percentage of iron oxide powder produced the highest COF and having slightly higher thickness loss as compared with sample utilising commercial carbon. Thus, the base formulation sample T2 is the best formulation which produce the optimum triblogical and mechanical result. The transisition of wear mechanism from abrasion to severe adhesion under high surface temperature may cause increase in wear rate of the friction material.